The Impact of COVID-19 on Users' Visit to the Shopping Centers in Libya - Almansouri, Hafith Mohammed Sulayman; Çetin, Mehmet (Izmir UOD, 2021)
The impacts of COVID-19 pandemic are expected to be challenging on all countries worldwide, especially from an economic concept. Reformations in the world’s economic system and changes in human precautions and behaviors are expected to influence several other aspects directly and indirectly. This paper aims to evaluate the impact of the pandemic on the behaviors and perceptions of shopping malls’ users. Through the performed questionnaire on the residents of Dernah, Libya, it was found that they depend on cars as a main mean of transportation. Thus, no major impacts were found on the user’s choices in that aspect. However, evaluations of the scale reflect changes of people’s attitudes towards their preferences for shopping malls. These results are significant indicators in directing the attention of designers and managers of shopping malls to adopt new strategies and approaches.
Keywords: 13. Climate action; 11. Sustainability; 1. No poverty; 3. Good health